Development and Characterization of a Chitosan and Polyvinyl Alcohol (CS/PVP)-Based Slow-Release Urea Fertilizer Membrane - Retno Ariadi Lusiana; Khabibi Khabibi; Rahmad Nuryanto; Muhammad Ridho Shofwan Al Aziz (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2024)
A slow-release test of urea fertilizer was conducted using chitosan-urea (CS-U) and chitosan/polyvinyl pyrrolidone K30-urea (CS/PVP-U) membranes. The urea membrane synthesis involved a blending method, with PVP K30 added as a component. The slow-release capabilities of CS-U, CS/PVP1-U, CS/PVP2-U, CS/PVP3-U, and CS/PVP4-U membranes were compared. FTIR results showed an increased intensity of the primary NH double peak at 1587 cm-1 and 1640 cm-1, while the C=O spectrum shifted from 1640 to 1647 cm-1 and the -OH group from 3354 cm-1 to 3362 cm-1, indicating hydrogen bond formation in CS/PVP-U. XRD analysis confirmed the membrane’s amorphous structure, and FE-SEM and AFM studies revealed morphology and roughness differences, with CS/PVP4-U having the largest cross-sectional diameter. The release study showed that PVP-modified chitosan membranes increased urea release, achieving 60 ppm/2 days for the first 16 days, then decreasing to about 55 ppm through day 30, with partial urea release controlled over time. This suggests that SRF fertilizer can effectively control urea release into the environment.